Superiority of urgent vs early endoscopic hemostasis in patients with upper gastrointestinal bleeding with high-risk stigmata. (2nd November 2021) - Horibe, Masayasu; Iwasaki, Eisuke; Matsuzaki, Juntaro; Bazerbachi, Fateh; Kaneko, Tetsuji; Minami, Kazuhiro; Fukuhara, Seiichiro; Masaoka, Tatsuhiro; Hosoe, Naoki; Ogura, Yuki; Namiki, Shin; Hosoda, Yasuo; et al.
Abstract: Background: Guidelines recommend that all patients with upper gastrointestinal bleeding (UGIB) undergo endoscopy within 24 h. It is unclear whether a subgroup may benefit from an urgent intervention. We aimed to evaluate the influence of endoscopic hemostasis and urgent endoscopy on mortality in UGIB patients with high-risk stigmata (HRS). Methods: Consecutive patients with suspected UGIB were enrolled in three Japanese hospitals with a policy to perform endoscopy within 24 h. The primary outcome was 30-day mortality. Endoscopic hemostasis and endoscopy timing (urgent, ≤6 h; early, >6 h) were evaluated in a regression model adjusting for age, systolic pressure, heart rate, hemoglobin, creatinine, and variceal bleeding in multivariate analysis. A propensity score of 1:1 matched sensitivity analysis was also performed. Results: HRS were present in 886 of 1966 patients, and 35 of 886 (3.95%) patients perished. Median urgent-endoscopy time ( n = 769) was 3.0 h (interquartile range [IQR], 2.0–4.0 h) and early endoscopy ( n = 117) was 12.0 h (IQR, 8.5–19.0 h). Successful endoscopic hemostasis and urgent endoscopy were significantly associated with reduced mortality in multivariable analysis (odds ratio [OR], 0.22; 95% confidence interval [CI], 0.09–0.52; P = 0.0006, and OR, 0.37; 95% CI, 0.16–0.87; P = 0.023, respectively). In a propensity-score-matched analysis of 115 pairs, adjusted comparisons showed significantly lower mortality of urgent vs early endoscopy (2.61% vs 7.83%, P < 0.001). Conclusions: A subgroup of UGIB patients, namely those harboring HRS, may benefit from endoscopic hemostasis and urgent endoscopy rather than early endoscopy in reducing mortality. Implementing triage scores that predict the presence of such lesions is important.